Wireless Mesh Networks Efficient Link Scheduling, Channel Assignment and Network Planning Strategies - Krendzel, Andrey V. (IntechOpen, 2012)
This book provides an in-depth look into recent advances in relation to novel design strategies and algorithms to improve performance and functionality of WMNs. Ten contributed chapters written by a group of well-known experts in wireless mesh networking are arranged in two parts. The first part of the book focuses on link scheduling schemes to select a subset of links for simultaneous transitions under interference constraints in an efficient and fair manner to guarantee a certain level of network connectivity. Besides, it describes channel assignment strategies to improve the network throughput in multi-radio multi-channel WMNs by means of an efficient channel utilization and minimization of the interference. The second part of the book addresses some important network planning issues related to efficient routing protocols in dynamic large-scale mesh environment, achievable capacity limit of a single wireless link between two multi-interface mesh nodes, the correctness of the mesh security architecture, fault-tolerant mesh network topology planning.